Prospects of using methods effective use of alternative energy - Bukhkalo, Svetlana; Olkhovska, Oksana (Publishing House of Lviv Polytechnic National University, 2016)
The article presents the possibility of the development of science-based concept of integrated processes complex enterprises energy mix (alternative energy and polymer wastes). A review of the literature and the necessary articles written on the subject: as technologies and economies develop and become more complex, energy needs increase greatly; types and methods of alternative energy, as well as the possibility of calculating the basic set of main economic indicators are classified; identified possible areas of work in obtaining the necessary information and results. The results of studies of complex innovative projects conducted as interuniversity cooperation.
Keywords: environmental safety; alternative energy; complex projects; polymer wastes; estimation criteria; scientifically grounded processes